¬ACTN3/ EXON-19 GENE POLYMORPHISM AND RELATIONSHIP WITH LOCAL HORSES PERFORMANCE IN IRAQ - W. Z. Turki,; N. N. Al-Anbari, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted to investigate the polymorphism of ACTN3/EXON-19 gene and their relationship the performance of local horses in Iraq. This study was carried out at the Iraqi Equestrian Club (15 km west from Baghdad city center) period during d from 1 February to 30 December 2022, to investigate the gene polymorphism of ACTN3 region EXON-19 and their relationship with performance of local horses in Iraq. Were found three variants (3 SNPs) in the ACTN3 gene - exon 19 and in different locations, namely rs1148960207, whose genotypes were CC, CT, and TT, as their distribution rates were significantly different (P≤0.05). The ratios of heterogeneity rs1144413495 with genotypes CC, TC, and TT were 34.21, 60.53, and 5.26% that differ significantly at (P≤0.01), with an allelic frequency of 0.64 and 0.36 for the two alleles C and T, respectively. The variant rs1148960207 had a significant (P≤0.05) effect on post-exercise breathing depth, speed rate and body length. Moreover a highly significant (P≤0.01) effect on heart girth and forefoot height for local horses. In conclusion ACTN3 gene has a distinct role in some physiological traits like the number and depth of respiration after exercise, rate of speed, and some body measurements, like body length, heart girth, and frontal height.